Ambiphilicity: A Characteristic Reactivity Principle of Pi-Bound Phosphorus Heterocycles - Clark, Timothy; Toepffer, Christian; Heinemann, Frank Wilhelm; Hennemann, Matthias; Zenneck, Ulrich; et al. (Angewandte Chemie International Edition, 2002)
Bicycles made in crystals: The phosphorus atoms of the: π ligand 1,3-diphosphete turn out to be ambiphilic centers with pronounced intramolecular reactivity. This property results in a temperature-dependent bond formation in [(2,4-di-tBu-1,3-diphosphete)3Mo], which is found to be a topotactic reaction in the single crystal (see scheme). This new reactivity principle can be used to explain a series of complex interligand bond-formation reactions of phosphorus heterocycles.
UnivIS-Import:2015-04-14:Pub.2002.forsch.sonder.sfb583.ambiph
Keywords: DFT calculations; Molybdenum; P ligands; Phosphorus heterocycles; Pi interactions; Solid-state reactions

Intramolecular Reactivity of Pi-Coordinated P-Heterocycles: How to Form Five-Membered Rings out of Phosphaalkynes - Clark, Timothy; Binger, Paul; Heinemann, Frank Wilhelm; Hennemann, Matthias; Pritzkow, Hans; Toepffer, Christian; Zenneck, Ulrich (Phosphorus Sulfur and Silicon and the Related Elements, 2002)
Experimental and theoretical evidence is presented for a novel metal-dependent intramolecular reactivity of π-bonded, unsaturated P-heterocycles like 1,3-diphosphete and 1,3,5-triphosphinine. The nucleophilic attack of a P lone pair of 1,3-diphosphete toward a neighboring ligand leads to new bicyclic ligands with unique structural features. A metal-initiated intramolecular hydrogen transfer and C-C bond formation are observed for (1,3,5-triphosphinine)(COD)Fe to result in the formation of [(CO)5Cr(4,5,6-trihydro-1,3,5-triphosphinine)(trihydropentalene) Fe].
UnivIS-Import:2015-04-14:Pub.2002.forsch.sonder.sfb583.intram
Keywords: DFT calculations; Iron; Molybdenum; P-heterocycles; π-complexes

Wave packet simulations for the insulator-metal transition in dense hydrogen - Jakob, B.; Reinhard, Paul-Gerhard; Toepffer, Christian; Zwicknagel, Günter (Journal of Physics A: Mathematical and Theoretical, 2009)
Dense hydrogen is studied in the framework of wave packet simulations. In this semi-quantal method the electrons are represented by wave packets which are suitably parameterized, e.g. Gaussians. The time evolution of the system and the equilibrium properties are obtained with the help of a variational principle and by Monte Carlo sampling, respectively. A transition from a molecular to a metallic state is observed. The wave packets become delocalized and the electrical conductivity increases sharply. The phase diagram is calculated in a wide range of the pressure-density-temperature space. In the transition from the molecular to the metallic state the density increases in agreement with recent reverberating shock wave experiments. © 2009 IOP Publishing Ltd.
CRIS-Team Scopus Importer:2023-07-24